2008
DOI: 10.4049/jimmunol.180.4.2019
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: A cis-Acting DNA Element Targets AID-Mediated Sequence Diversification to the Chicken Ig Light Chain Gene Locus

Abstract: Somatic hypermutation and gene conversion are two closely related processes that increase the diversity of the primary Ig repertoire. Both processes are initiated by the activation-induced cytidine deaminase that converts cytosine residues to uracils in a transcription-dependent manner; these lesions are subsequently fixed in the genome by direct replication and error-prone DNA repair. Two alternative mechanisms were proposed to explain why this mutagenic activity is targeted almost exclusively to Ig loci: 1) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(64 citation statements)
references
References 25 publications
2
61
1
Order By: Relevance
“…However, none of the known transcriptional control elements in mouse B cells appears to be absolutely required for SHM, suggesting a redundancy or unidentified elements (48). Recent studies discovered novel cis-acting elements in the IgL locus of the DT40 chicken B cell line that are both essential and sufficient for AIDmediated sequence diversification (59,60). In addition, it was shown that CAGGTG cis elements in the context of Ig enhancers were sufficient and essential to target mutations to a nearby transcribed gene in transgenic DT40 cell lines (61).…”
Section: Discussionmentioning
confidence: 99%
“…However, none of the known transcriptional control elements in mouse B cells appears to be absolutely required for SHM, suggesting a redundancy or unidentified elements (48). Recent studies discovered novel cis-acting elements in the IgL locus of the DT40 chicken B cell line that are both essential and sufficient for AIDmediated sequence diversification (59,60). In addition, it was shown that CAGGTG cis elements in the context of Ig enhancers were sufficient and essential to target mutations to a nearby transcribed gene in transgenic DT40 cell lines (61).…”
Section: Discussionmentioning
confidence: 99%
“…Deletion of 3'E reduced transcription but did not affect SHM (Inlay et al ., 2006; van der Stoep et al ., 1998), whereas deletion of Ed reduced both transcription and SHM (Xiang and Garrard, 2008). Likewise, the chicken Ig λ locus has a defined 3'E (Bulfone-Paus et al ., 1995) and another downstream enhancer, 3'RR (Kothapalli et al ., 2008). In the DT40 cell line, deletion of the 3'E had no effect on SHM (Yang et al ., 2006), but deletion of 3'RR ablated transcription and SHM (Kothapalli et al ., 2008).…”
Section: The Targeting Enigmamentioning
confidence: 99%
“…Thus far, germline deletion of Ig enhancers has resulted in either normal SHM, or impaired SHM accompanied by reduced transcription. Interestingly, recent studies in the chicken DT40 B-cell line identified a large DNA region 3 0 of the Igl constant region with apparent SHM targeting activity [56,57].…”
Section: Box 1 the Targeting Of Shmmentioning
confidence: 99%